Correlation of ocular ultrasonography with histopathologic findings in intraocular retinoblastoma - Romeo B. Espiritu, MD; Eric G. Valera, MD; Arnel A. de Jesus, MD; Yasmyne C. Ronquillo, MD; Gary V. Mercado, MD (Philippine Journal of Ophthalmology)
Objective: This study correlated the patterns of ocular B- and A-scans of intraocular retinoblastoma (RB) with corresponding histopathology sections. It aimed to establish a more objective basis for determining intraocular retinoblastoma by ultrasonography (UTZ) and to determine the degree of malignancy and viability of the tumor cells.